PENGARUH BRAND IMAGE, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA DUNKIN CABANG METRO PERMATA, TANGERANG - Yulieana Yulieana; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
Currently, the food & beverages business faces intense competition in Indonesia, one of which is in selling donuts. Dunkin is a company in the food & beverages sector that sells donuts as its main product. This study is motivated by Dunkin experiencing a slowdown in growth, which is supported by J.Co as its main competitor, expanding with additional product varieties and branches in Indonesia. Moreover. The author's objective in this research is to understand the influence of Brand Image, price perception, and promotion on purchase decisions, and to identify alternative solutions to address the increasing purchase decision issue. The research method employed is quantitative associative, collecting questionnaire data from 100 respondents who are Dunkin customers at the Metro Permata branch in Tangerang, using the Lemeshow formula due to an unknown exact population size. SPSS 25 was used to process the data. Based on the findings of this research, it shows that Brand Image, price perception have an influence on purchase decisions, and promotion does not have an influence on purchase decisions.